Labor market closure and the stalling of the gender pay gap - Lara Minkus (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
The gender pay gap (GPG) remains a persistent phenomenon in contemporary labor markets. Despite a vast body of research examining its causes, as of today, unequal labor market power resources between men and women have remained an underappreciated factor in the literature. Drawing on the Socio-economic Panel and the Microcensus, the association between the GPG and labor market closure - a crucial determinant of unequal power resources in labor markets - is followed from 1993-2011. Employing JMP decomposition, unionization, tertiary credentialing and part-time employment are found to exacerbate the overall wage differential by 41 percent. Part-time employment has been the only indictor that enlarged the gender pay gap (17 percent) between 1993 and 2011, while the remaining covariates contributed toward its convergence. These results advance our understanding of stalling GPGs by highlighting the so far widely neglected importance of power resources on the GPG.
Keywords: J2; J5; L1; 330; gender pay gap; labor market closure; stalled gender revolution; JMP decom-position; dualism